A review of personality factors on infidelity - Tan, Lin Jia; Hwong, Kah Ing; Lee, Michelle Chin Chin (Penerbit Universiti Kebangsaan Malaysia, 2016)
The current paper review researches on sexual and online infidelity from personality perspectives. This is done through looking from Dark Triad Traits, The Big Five Factors and HEXACO. 51 studies from various journals were reviewed and showed supportive findings between personality and infidelity. Individuals high in the Dark Triads: psychopathy, narcissism, and Machiavellianism were associated with committing infidelity. For the Big Five Factors, conscientiousness was linked to lower infidelity; extraversion and agreeableness were associated with higher infidelity while neuroticism and openness showed mixed results. For HEXACO, individuals scoring low on honesty-humility scale had stronger relationship with infidelity. Future studies should do more studies on neuroticism and openness on infidelity. Environment factors should also be considered in explaining individuals’ act in committing infidelity.